CONCEPTUAL ASPECTS OF IMPLEMENTATION OF INFORMATION EDUCATIONAL ENVIRONMENT FOR THE TRAINING OF BACHELORS IN HIGHER EDUCATION - Isaeva, P.M. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2017)
The article describes aspects of the implementation of information and educational environment in order to implement the priorities for the development and implementation of innovative distance learning technologies for the transition from a traditional institution in the model of the innovation Institute, which connects professional, cultural or scientific competence of bachelors. The essence of the problem ongoing research is the need to achieve efficiency new quality of education, i.e. the transition to a higher level of preparation of bachelors.In accordance with the requirements of Federal state educational standard of higher education in conditions of modernization of education, teacher’s professional work is increasingly associated with innovative research innovative research of the educational process.It was the introduction of electronic information-educational environment is one of the main directions for the preparation of future bachelors and forces to reconsider their views on the content of the educational system. Describes the experience of creation of information-educational environment of Pyatigorsk state linguistic University on the basis of Moodle. Thanks to the creation of information-educational environment in high schools, teachers, parents, and students aware of all the events of the learning process and in the world of science and, moreover, this system gives you the opportunity to maintain close communication with teachers and between students.